UJI ORGANOLEPTIK PROBIOTIK BAKTERI ASAM LAKTAT ASAL SUSU KUDA SUMBA DALAM KEMASAN BERBEDA - Foeh, Nancy; Datta, Frans Umbu; Detha, Annytha; Ndaong, Nemay; Kallau, Novalino; Tulasi, Maria (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
The purpose of this study was to examine the shelf life of lactic acid probiotics from Sumba horse milk in various packages. The study was conducted from August to November 2021. Lactic acid bacteria were cultured from Sumba horse milk, stored in MRS Broth. These lactic acid bacteria were diluted with concentrations of 10%, 20%, and 30%, respectively, and packaged in glass bottles, plastic bottles High-Density Polyethylene (HDPE), and plastic clips/ polypropylene standing pouch. Packaged probiotics were stored at room temperature for 14 days. The results showed that storage using High-Density Polyethylene (HDPE) and plastic clips was better than glass bottles. The study concluded that a concentration of 30% in plastic bottle High-Density Polyethylene (HDPE) packaging was preferred in organoleptic testing